Gait ground reaction force characteristics in children with and without forward head posture - AmirAli Jafarnezhadgero; Hamed Sheikhalizade (Journal of Kerman University of Medical Sciences, 2019)
Background: Forward head posture is one of the most prevalent abnormal postures in patients with neck disorders. The aim of this study was to evaluate the effects of forward head posture on gait ground reaction force characteristics in children. Methods: Twelve children with forward head posture (age: 11.8±1.3 years) and sixteen healthy control children (age: 11.7±1.4 years) volunteered to participate in this study. Each participant was asked to walk 10 m in six trials with self-selected speed. The ground reaction force was measured by two Kistler Force Platforms at a frequency of 1000 Hz. MANOVA test ((version 16, SPSS Inc, Chicago, Il)) was used for between group comparisons. Results: In the non-dominant limb, the medio-lateral ground reaction force during push off phasein the forward head group was greater than that in the healthy group by 22.1% (P=0.049). In the dominant limb, time to peak for vertical ground reaction force during heel contact(by 13.7%; P=0.015) and push off(by 14.2%; P=0.004), mediolateral ground reaction force during heel contact (by 46.0%; P=0.006) and push off (by 15.1%; P=0.039) in the forward head group were significantly lower than those in the healthy group. Vertical loading, peak positive and negative free moment, and impulses in all axes were similar in the healthy and the forward head groups (P>0.05). Conclusion: Overall, the results reveal that gait ground reaction force components (especially time to peak for ground reaction forces) in forward head children may have clinical importance for the improvement of walking mechanics of these individuals. Rehabilitation protocols should be designed to increase time to reach peak ground reaction forces and decrease medio-lateral ground reaction force in forward head children during walking.